Application Progress of Artificial Intelligence in the Diagnosis and Treatment of Diabetes and Its Complications - Niu, Yiqing (Journal of Contemporary Medical Practice, 2025)
Diabetes is a global chronic disease, and its diagnosis and treatment process faces many challenges such as precision, individualization and prevention and control of complications. Artificial intelligence (AI) technology has shown great transformative potential in the whole process of diabetes diagnosis and treatment with its ability to integrate multimodal data. This article discusses the application of AI in the early screening and diagnosis of diabetes, blood glucose management and treatment optimization, and complication prediction and management, and analyzes the challenges and future development direction, so as to provide a reference for research and clinical practice in the field of endocrinology.